Analysis of the Role of the Inspectorate in the Implementation of Regional Autonomy Supervision in Deli Serdang Regency - Tria Wardani; Nur Ahmad Bi Rahmani (Penerbit Jurnal Indonesia, 2022)
Currently each region has the authority in terms of regulating its own region, of course this is a lot of questions for some people. The right to regional autonomy provides leeway for each region to regulate their respective regions even from an economic point of view. From this phenomenon, it is necessary to have an inspectorate that functions as a supervisor of every government administration so as to provide reporting on all actions taken by the regional government. The purpose of this study was to determine the role of the inspectorate carried out in Deli Serdang Regency on the regional autonomy rights of Deli Serdang Regency itself. The research method used is a qualitative research method. The results showed that the Deli Serdang Regency inspectorate had carried out their duties well. This form of supervision is carried out by implementing regular checks on all forms of mobilization of government officials..